Управління економічним розвитком установи в умовах турбулентного середовища - Шадурський, Костянтин Олександрович; Shadurskyi, Kostiantyn (ЦНТУ, 2024)
Метою дослідження є розробка ефективних підходів та стратегій управління економічним розвитком установ в умовах турбулентного середовища, що включає аналіз існуючих методів, виявлення основних факторів впливу та розробку рекомендацій для підвищення стійкості та адаптивності організацій до швидких змін. Завданнями роботи є: розглянути теоретичні аспекти управління економічним розвитком вітчизняних установ; вивчити підходи та критерії оцінювання рівня економічного розвитку установи; визначити специфічні риси управління економічним розвитком установи в контексті турбулентних змін; зробити комплексну оцінку стану економічного розвитку установи; виявити напрями активізації економічного розвитку установи в умовах турбулентного середовища. The aim of the study is to develop effective approaches and strategies for managing the economic development of institutions in a turbulent environment, including analysis of existing methods, identification of the main factors of influence and development of recommendations to increase the sustainability and adaptability of organizations to rapid change. The objectives of the study are: to consider the theoretical aspects of managing the economic development of domestic institutions; to study the approaches and criteria for assessing the level of economic development of an institution; to identify specific features of managing the economic development of an institution in the context of turbulent changes; to make a comprehensive assessment of the state of economic development of an institution; to identify areas for enhancing the economic development of an institution in a turbulent environment.
Management of the establishment's economic development in the turbulent environment
Keywords: економічний розвиток; турбулентне середовище; комплексна оцінка; economic development; turbulent environment; comprehensive assessment